2012
DOI: 10.1891/0886-6708.27.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Examining Gender Differences in the Relationship Between Dating Violence Victimization and Anger in College Students

Abstract: It has been well established that dating violence victimization is associated with various mental health problems. Relatively, little is known about similarities and differences between mental health correlates of dating violence victimization for males and females. We examined the associations between physical and psychological victimization experiences and measures of anger in a sample of 200 male and female undergraduates. Results suggest that men's victimization was more strongly associated with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
11
1
1
Order By: Relevance
“…These findings are inconsistent with those of a previous study that found anger to be more strongly associated with IPV victimization among men than women (Rutter et al, 2012); however, variations in study methodologies may account for inconsistent findings between studies, including differences in the measures of anger. Because both childhood family violence exposure and IPV are prevalent among women and men, potential sex differences and similarities should continue to be examined in future research.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings are inconsistent with those of a previous study that found anger to be more strongly associated with IPV victimization among men than women (Rutter et al, 2012); however, variations in study methodologies may account for inconsistent findings between studies, including differences in the measures of anger. Because both childhood family violence exposure and IPV are prevalent among women and men, potential sex differences and similarities should continue to be examined in future research.…”
Section: Discussioncontrasting
confidence: 99%
“…A secondary aim of this study was to explore these associations in men and women because there may be gender differences in psychosocial functioning and IPV risk following family violence exposure (Afifi et al, 2008; Desai et al, 2002; Iverson et al, 2011). Similarly, prior work suggests that the strength of the associations between anger-related dysregulation and IPV may differ by gender (Rutter et al, 2012). …”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Analyses were conducted separately for males and females due to potential sex differences in DV (Rutter et al, 2012; Shorey et al, 2011), using MPlus version 6.11 (Muthén and Muthén, 2010). Comparison group participants were grouped with violent injury participants because comparisons could have experienced DV prior to ED visit.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates suggest that anywhere from 10 to 92% of college students experience physical dating violence (Forke, Myers, Catallozzi, & Schwarz, 2008;Harned, 2001Harned, , 2002Hines & Saudino, 2003;Knox, Custis, & Zusman, 2000;Lane & Gwartney-Gibbs, 1985;Makepeace, 1981;Rhatigan & Street, 2005;Rutter, Weatherill, Taft, & Orazem, 2012;Straight, Harper, & Arias, 2003;Straus, 2004). In a longitudinal study including more than 1,000 female university students, Smith, White, and Holland (2003) found that 88% of the women in their sample reported at least one physical or sexual IPV victimization between adolescence and their fourth year of college.…”
Section: Literature Reviewmentioning
confidence: 99%